The memories of PIBID in the construction of teaching subjectivities: notes on the practices of public history taught. - Delfino, Leonara (Educação, Escola & Sociedade, 2021)
Abstract: The article aims to analyze the construction of teaching subjectivities, crossed by emancipatory practices and approaches developed by collective actions between school subjects and Pibidian teams of the history course at the Federal University of Alfenas (UNIFAL) in public schools in that city, between 2014- 2017. The selected projects refer to those dedicated to living pasts, especially the themes of African, Afro-Brazilian and indigenous cultures, in reference to Laws 10.639/2003 and 11.645/2008, whose curricular changes reformulated the Law of National Guidelines and Bases (LBDN). Our study is based on Taught Public History and decolonial pedagogy to think about subaltern themes in the prescribed and practiced curricula, such as the History of Africa and the historical protagonism of non-white subjects, as elements of decentering for the construction of historical consciousness and subjectivities of teachers in training. For this, we use the methodology of oral history, in addition to the qualitative analysis of reports, assessments of diagnoses and intervention projects by PIBID.